Opioid Use and Misuse and Suicidal Behaviors in a Nationally Representative Sample of US Adults. Issue 7 (5th March 2019) - Samples, Hillary; Stuart, Elizabeth A; Olfson, Mark
Abstract: Prior research has shown associations between opioid misuse and suicidal behaviors, but the relationship between medical opioid use and suicidal behaviors is not known. We assessed associations of opioid use and misuse with suicidal ideation, suicide plans, and suicide attempts among adults aged 18–64 years ( n = 86, 186) using nationally representative cross-sectional data from the 2015 and 2016 administrations of the National Survey on Drug Use and Health. We used logistic regression to estimate associations between opioid use/misuse and suicidal behaviors and propensity score–weighted logistic regression analysis to examine the counterfactual scenario in which persons with misuse had instead not misused opioids. In propensity score–weighted analyses, compared with opioid misuse, opioid use without misuse was associated with lower odds of suicidal ideation (odds ratio (OR) = 0.57, 95% confidence interval (CI): 0.45, 0.72) and suicide plans (OR = 0.53, 95% CI: 0.35, 0.80), and no use was associated with lower odds of suicidal ideation (OR = 0.62, 95% CI: 0.49, 0.80), suicide plans (OR = 0.56, 95% CI: 0.39, 0.79), and suicide attempts (OR = 0.54, 95% CI: 0.33, 0.89). These findings suggest that opioid misuse is associated with greater odds of suicidal behaviors, but opioid use without misuse is not. Compared with persons with opioid misuse, similar persons without misuse have a reduced risk of suicidal behaviors. Clinical and public health interventions should focus on preventing misuse of opioids.